Product Design Process Optimization at Small Business - Jerkovič, Martin; Buchalcevová, Alena, 1958-; Mittner, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
Thesis deals with design process optimization at Chute Corporation -- american startup that provides SaaS solutions for discovery, gathering, managing, publishing and analysis of multimedial user-generated content from social networks. The goal is to identify and analyze the processes, roles and tools of product design and propose an optimization. Thesis has two parts. First part describes the theoretical background for later application. Mainly a brief history of IT product design, design taxonomy and design workflow best practices are described. The other part provides a brief description of the company, especially its position on the market, business model, organizational structure, product portfolio, position of product team and also identifies the main processes, roles and tools that surround product design. The final part describes all optimized processes, roles and tools and summarizes all the facts as a set of recommendations. Thesis provides an overview of product design in the dynamic and complex world of startups. The specific recommendations and templates of optimized processes and tools enable immediate implementation into a company of a similar nature.
Vedoucí práce: Alena Buchalcevová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses